Immunoreactivity of Vesicular Glutamate Transporter 2 Corresponds to Cytochrome Oxidase-Rich Subcompartments in the Visual Cortex of Squirrel Monkeys - Yao, Songping; Zhou, Qiuying; Li, Shuiyu; Takahata, Toru (Frontiers in Neuroanatomy, 2021)
Cytochrome oxidase (CO) histochemistry has been used to reveal the cytoarchitecture of the primate brain, including blobs/puffs/patches in the striate cortex (V1), and thick, thin and pale stripes in the middle layer of the secondary visual cortex (V2). It has been suggested that CO activity is coupled with the spiking activity of neurons, implying that neurons in these CO-rich subcompartments are more active than surrounding regions. However, we have discussed possibility that CO histochemistry represents the distribution of thalamo-cortical afferent terminals that generally use vesicular glutamate transporter 2 (VGLUT2) as their main glutamate transporter, and not the activity of cortical neurons. In this study, we systematically compared the labeling patterns observed between CO histochemistry and immunohistochemistry (IHC) for VGLUT2 from the system to microarchitecture levels in the visual cortex of squirrel monkeys. The two staining patterns bore striking similarities at all levels of the visual cortex, including the honeycomb structure of V1 layer 3B (Brodmann’s layer 4A), the patchy architecture in the deep layers of V1, the superficial blobs of V1, and the V2 stripes. The microarchitecture was more evident in VGLUT2 IHC, as expected. VGLUT2 protein expression that produced specific IHC labeling is thought to originate from the thalamus since the lateral geniculate nucleus (LGN) and the pulvinar complex both show high expression levels of VGLUT2 mRNA, but cortical neurons do not. These observations support our theory that the subcompartments revealed by CO histochemistry represent the distribution of thalamo-cortical afferent terminals in the primate visual cortex.